Critical reflection on required service to the community propels prospective medical students toward higher empathy, compassion, and bias mitigation but are these gains sustainable? - Van Winkle, Lon J.; Thornock, Bradley O.; Schwartz, Brian D.; Horst, Alexis; Fisher, Jensen A.; Michels, Nicole (Frontiers in Medicine, 2022)
Purpose We observed increased cognitive empathy and reflective capacity scores when prospective medical students wrote critical reflections on mandatory team service-learning in a Medical Humanities course, but these findings did not include a control group. Here we compare these survey results in similar courses with and without required service-learning. Methods Forty-three prospective medical students completed a Medical Humanities course requiring critical reflection on team service-learning. In comparison, 32 students finished a similar course in which service to the community was not mandatory. Before starting the courses, students completed reliable surveys of their cognitive empathy and reflective capacity, and more than 93% of the students completed the same surveys after finishing the courses. Results Students' cognitive empathy and reflective capacity scores increased significantly when service-learning was required, but the scores did not increase significantly when service to the community was not required. The effect size for the empathy increase was of crucial practical importance (r = 0.50), whereas it was of moderate practical importance for the increase in reflective capacity (r = 0.34). Conclusions These and prior findings strongly support the conclusion that students' critical reflection on mandatory team service-learning fosters development of their cognitive empathy and reflective capacity. We present a model program to incorporate critical reflection on service to the community throughout the curricula of all healthcare professions trainees.